EFEKTIVITAS PENGEMBANGAN PARIWISATA DI KABUPATEN SINTANG - Syahrul Tri Ubargi E.42009033 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
The purpose of this study is to analyze the effectiveness of Culture and Tourism in developing Sintang Attractions Bukit Tenebrous. Through adaptation, integration, motivation, and production is carried out by the Department of Culture and Tourism.Through a qualitative approach, this study found that the effectiveness of the development of tourism in particular Sintang Attractions Bukit Tenebrous through programs run by the Department of Tourism Sintang culture and yet with maximum due to several constraints such as the lack of accommodation facilities and infrastructure such as base , eating houses and arena games and entertainment, poor transport infrastructure towards Bukit Tenebrous area attractions as well as the lack of promotional materials that resulted in the promotion activities less than the maximum. In addition, the Department of Culture and Tourism as the implementor Sintang policy is not supported by adequate human resources, thus achieving the target of tourist visits in Bukit dark attractions can be achieved with the maximum bulum. Keywords: Effectifity, Tourism Development.